Method for measuring hydrogen diffusion coefficient in alloy structural steel large-size forge piece

The determination of the hydrogen diffusion coefficient in large forgings of alloy structural steel through electrochemical hydrogen charging method and TDS equipment has solved the problem that is difficult to accurately determine in the prior art, provided a scientific basis for the dehydrogen annealing process, and improved the stability of tissue performance.

CN119804231APending Publication Date: 2025-04-11CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411899882.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

It is difficult for the prior art to accurately determine the hydrogen diffusion coefficient in large forgings of alloy structural steel, resulting in the lack of theoretical basis for the dehydrogenation process parameters and affect performance stability.

Method used

After the sample was filled with hydrogen in alkali solution by electrochemical hydrogen charging method, and placed at room temperature for different times, the hydrogen content was measured using TDS equipment and the hydrogen diffusion coefficient was calculated by fitting the formula.

Benefits of technology

The accurate determination of the hydrogen diffusion coefficient in large forgings of alloy structural steel is achieved, and scientific basis is provided to optimize the dehydrogen annealing process and improve the stability of tissue performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119804231A_ABST
    Figure CN119804231A_ABST
Patent Text Reader

Abstract

The invention relates to a method for measuring a hydrogen diffusion coefficient in an alloy structural steel large-size forge piece, belongs to the technical field of alloy structural steel large forge pieces, and aims to solve the problem of the hydrogen diffusion coefficient of the alloy structural steel large-size forge piece which is not disclosed in the prior art. According to the testing method, firstly, electrochemical hydrogen charging is conducted on the sample, the hydrogen content is measured through TDS after the sample subjected to hydrogen charging is placed at the room temperature for different times, and accurate values of hydrogen diffusion coefficients of different parts of the forge piece can be obtained according to the change rule of the hydrogen content along with the placement time; therefore, the diffusion behavior of hydrogen in the large forging can be better understood, and the dehydrogenation annealing process can be guided. The method can be popularized and applied to other steel and alloy material large forgings, and the hydrogen measurement precision of the method reaches 0.01 ppm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of large alloy structural steel forgings, and in particular to a method for measuring the hydrogen diffusion coefficient in large-size alloy structural steel forgings. Background Art

[0002] Large alloy structural steel forgings are widely used in energy equipment, rail transit equipment and other fields. The technical difficulty lies in the fact that large size can easily lead to uneven structure and performance, and even cause serious defects and scrap. The structure characteristics of large alloy structural steel forgings with a thickness of more than 100 mm are usually different at different thicknesses, and there are microscopic differences even if the structure type is the same. The diffusion coefficient of hydrogen in steels with different structures is also different.

[0003] The harmful effects of hydrogen in high-strength steel are very significant. A very small amount of hydrogen may cause the performance of high-strength steel to deteriorate, and sometimes even cause hydrogen embrittlement. For large forgings of alloy structural steel, excessively high hydrogen content will lead to a decrease in plasticity and toughness. In severe cases, defects such as white spots may occur, resulting in the scrapping of parts. Therefore, a dehydrogenation annealing process must be adopted during the cooling process of large-sized forgings of alloy structural steel. The effect of hydrogen removal during dehydrogenation annealing is related to both the size of the large forgings and the diffusion coefficient of hydrogen in steel. The currently used dehydrogenation annealing processes, such as key parameters such as temperature and time, lack a theoretical basis for the diffusion coefficient of hydrogen in large forgings, resulting in either too long a time to waste energy, or insufficient time to cause performance fluctuations.

[0004] Due to limited testing methods, the hydrogen content and diffusion coefficient of hydrogen in steel cannot be accurately measured for a long time. The usual gas analysis method for hydrogen content in steel can only accurately measure above 0.5ppm, and accurate values ​​cannot be obtained below 0.5ppm, so it is difficult to accurately calculate the hydrogen diffusion coefficient based on the usual measurement results; and the hydrogen permeation method is only suitable for measuring the hydrogen diffusion coefficient in thin-sheet specimens, and is not applicable to the hydrogen diffusion coefficient in large forgings of alloy structural steel. Therefore, it is necessary to find a suitable method to accurately measure the hydrogen diffusion coefficient of different parts in large forgings of alloy structural steel, so as to better understand the diffusion behavior of hydrogen in large forgings, formulate a more suitable dehydrogenation annealing process, and ensure good organizational properties. Summary of the invention

[0005] In view of the above analysis, the present invention aims to provide a method for determining the hydrogen diffusion coefficient in large-size forgings of alloy structural steel, so as to solve the problem that the existing method for determining the hydrogen diffusion coefficient of large-size forgings of alloy structural steel is not disclosed.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for determining the hydrogen diffusion coefficient in a large-size forging of alloy structural steel comprises the following steps:

[0008] (1) Sample preparation: Take samples from the locations to be tested on large-size alloy structural steel forgings and polish the sample surfaces;

[0009] (2) Electrochemical hydrogen charging: The sample is used as the cathode and Pt wire or graphite is used as the anode to perform electrochemical hydrogen charging in an alkaline solution;

[0010] (3) Storage test: The hydrogen-filled samples were placed at room temperature for different periods of time;

[0011] (4) TDS hydrogen measurement: Use TDS equipment to test the hydrogen content of samples at the same sampling thickness after being placed for different times;

[0012] (5) Calculation of hydrogen diffusion coefficient: Based on the hydrogen content of the sample at the same sampling thickness at different placement times tested in step (4), the relationship between the sample at the same sampling thickness at different placement times and the hydrogen content is fitted according to the following formula to obtain the hydrogen diffusion coefficient;

[0013] C t =C ∞ +(C0-C ∞ )exp(-22.2D t / d 2 );

[0014] Among them, C t is the hydrogen content in the sample after t hours of storage, unit: ppm; C ∞ is the hydrogen content in the sample after being placed for ≥48h, unit: ppm; C0 is the hydrogen content in the sample without being placed, unit: ppm; d is the sample diameter, unit: mm; D is the hydrogen diffusion coefficient, unit: cm 2 / s; t is the placement time, unit: h.

[0015] Furthermore, in step (1), the diameter of the sample is 5 mm and the length is 50 mm.

[0016] Furthermore, in step (1), at least 5 samples are taken at the same thickness position.

[0017] Furthermore, in step (2), the alkaline solution is a sodium hydroxide solution.

[0018] Furthermore, in step (2), the current in the electrochemical hydrogen charging is 10 to 100 mA, and the current density is 0.6 to 6 mA / cm 2 , continuous hydrogen charging for 48 to 96 hours.

[0019] Furthermore, in step (2), multiple samples taken at the same thickness position are connected in series and then electrochemically charged with hydrogen.

[0020] Furthermore, in step (3), the placement time is T0=0h, T1=12h, T2=24h, T3=48h, T4=96h...T n =2*T n-1 , where n is an integer ≥ 2.

[0021] Furthermore, in step (3), the temperature of the sample is 20±5°C.

[0022] Furthermore, in step (4), when testing the hydrogen content, the heating rate is 100-200°C / min and the heating temperature is 600-800°C.

[0023] Furthermore, in step (4), when testing the hydrogen content, the preparation time for the sample to enter the vacuum tube shall not exceed 10 minutes, and the difference in preparation time between different samples shall not exceed 1 minute.

[0024] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0025] The testing method of the present invention firstly performs electrochemical hydrogen charging on the sample, and then uses TDS to measure the hydrogen content of the sample after being placed at room temperature for different periods of time. The accurate value of the hydrogen diffusion coefficient of different parts of the forging can be obtained by the variation law of the hydrogen content with the placement time, so as to better understand the diffusion behavior of hydrogen in large forgings and guide the dehydrogenation annealing process. The method can be extended to other large forgings of steel and alloy materials, and the hydrogen measurement accuracy of the method of the present invention reaches 0.01ppm.

[0026] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0028] Figure 1 A physical picture of a sample in Example 1 of the present invention;

[0029] Figure 2 This is a picture of an electrochemical hydrogen charging in Example 1 of the present invention;

[0030] Figure 3 A picture of the TDS device in the present invention;

[0031] Figure 4A TDS curve of the present invention;

[0032] Figure 5 This is a curve showing the change of hydrogen content in the sample at the same sampling thickness in Example 1 of the present invention at different storage times. DETAILED DESCRIPTION

[0033] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0034] A specific embodiment of the present invention discloses a method for determining the hydrogen diffusion coefficient in a large-size forging of alloy structural steel, comprising the following steps:

[0035] (1) Sample preparation: Take samples from the locations to be tested on large-size alloy structural steel forgings and polish the sample surfaces;

[0036] (2) Electrochemical hydrogen charging: The sample is used as the cathode and Pt wire or graphite is used as the anode to perform electrochemical hydrogen charging in an alkaline solution;

[0037] (3) Storage test: The hydrogen-filled samples were placed at room temperature for different periods of time;

[0038] (4) TDS hydrogen measurement: Use TDS equipment to test the hydrogen content of samples at the same sampling thickness after being placed for different times;

[0039] (5) Calculation of hydrogen diffusion coefficient: Based on the hydrogen content of the sample at the same sampling thickness at different placement times tested in step (4), the relationship between the sample at the same sampling thickness at different placement times and the hydrogen content is fitted according to the following formula to obtain the hydrogen diffusion coefficient;

[0040] C t =C ∞ +(C0-C ∞ )exp(-22.2D t / d 2 );

[0041] Among them, C t The hydrogen content in the sample after t hours of storage, unit: h, C ∞ is the hydrogen content in the sample after being placed for ≥48h, unit: ppm, C0 is the hydrogen content in the sample without being placed, unit: ppm, d is the sample diameter, unit: mm, D is the hydrogen diffusion coefficient, unit: cm 2 / s, t is the placement time, unit: h.

[0042] The testing method of the present invention firstly performs electrochemical hydrogen charging on the sample, and then uses TDS to measure the hydrogen content of the sample after being placed at room temperature for different periods of time. The accurate value of the hydrogen diffusion coefficient of different parts of the forging can be obtained by the variation law of the hydrogen content with the placement time, so as to better understand the diffusion behavior of hydrogen in large forgings and guide the dehydrogenation annealing process. The method can be extended to other large forgings of steel and alloy materials, and the hydrogen measurement accuracy of the method of the present invention reaches 0.01ppm.

[0043] It should be noted that the large-size forgings of alloy structural steel described in the present invention refer to those with a thickness greater than 100 mm. Since the hydrogen content at the same thickness of large-size forgings is substantially the same, the method of the present invention selects samples at different thicknesses for experiment.

[0044] Specifically, in step (1), the positions to be tested include the near surface, 1 / 4 thickness and 1 / 2 thickness positions of the large-size forging, but are not limited to the above positions, and the sampling positions can be selected as needed. Since the hydrogen content of the large-size forging at the same thickness is basically the same, the method of the present invention selects samples at different thicknesses for experiment.

[0045] Specifically, in step (1), the diameter of the sample is 5 mm and the length is 50 mm.

[0046] Specifically, in step (1), at least 5 samples are taken at the same thickness position.

[0047] Specifically, in step (2), the alkaline solution is a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is 0.1 mol / L.

[0048] Specifically, in step (2), the current in the electrochemical hydrogen charging is 10 to 100 mA, for example, 10 mA, 20 mA, 30 mA, 40 mA, 50 mA, 60 mA, 70 mA, 80 mA, 90 mA, 100 mA, and the current density is 0.6 to 6 mA / cm 2 , for example, 0.6 mA / cm 2 , 1mA / cm 2 , 1.5mA / cm 2 , 2mA / cm 2 , 2.5mA / cm 2 , 3mA / cm 2 , 3.5mA / cm 2 , 4mA / cm 2 , 4.5mA / cm 2 , 5mA / cm 2 , 5.5mA / cm 2 , 6mA / cm 2 , continuously charge with hydrogen for 48 to 96 hours, for example, 48 hours, 60 hours, 72 hours, 84 hours, 96 hours.

[0049] It should be noted that before electrochemical hydrogen charging, the sample to be tested needs to be ultrasonically cleaned, clamped with a sample clamp and placed in a sodium hydroxide solution as a cathode, and the anode is also placed in a sodium hydroxide solution. Then the cathode and anode are connected to the positive and negative electrodes of a constant current power supply respectively. The current is 10-100 mA and the current density is 0.6-6 mA / cm 2 , continuous hydrogen charging for 48 to 96 hours.

[0050] Specifically, in step (2), multiple samples taken at the same thickness position are connected in series and then electrochemically charged with hydrogen.

[0051] Exemplarily, in step (3), the placement time is T0=0h, T1=12h, T2=24h, T3=48h, T4=96h...T n =2*T n-1 , wherein n is an integer ≥ 2. Preferably, n is 4.

[0052] Specifically, in step (3), the temperature at which the sample is placed is 20±5°C.

[0053] Specifically, in step (4), the TDS equipment is an existing equipment, and the manufacturer is R-DEC Company.

[0054] Specifically, in step (4), when testing the hydrogen content, the preparation time for the sample to enter the vacuum tube shall not exceed 10 minutes, and the difference in preparation time between different samples shall not exceed 1 minute.

[0055] It should be noted that the principle of using TDS equipment to test hydrogen content is to place the sample to be tested in a vacuum environment, increase the diffusion rate by heating, so that the hydrogen in the sample escapes, and then use a high-precision mass spectrometer to measure the rate and content of hydrogen escape, so as to accurately obtain the hydrogen content in the sample. Among them, the hydrogen content measurement accuracy of the TDS equipment can reach 0.01ppm.

[0056] Specifically, in step (4), when the hydrogen content is tested, the heating rate is 100-200°C / min, for example, 100°C / min, 120°C / min, 140°C / min, 160°C / min, 180°C / min, 200°C / min, and the heating temperature is 600-800°C, for example, 600°C, 650°C, 700°C, 750°C, 800°C.

[0057] It should be noted that if the heating rate is too low, the test time will be longer; if the heating rate is too high, the quartz tube in the equipment will be at risk of cracking; if the heating temperature is too low, the hydrogen may not escape completely; if the heating temperature is too high, the sample may have undergone a phase change.

[0058] The samples without samples and samples placed for different periods of time are placed in the TDS equipment to measure the hydrogen content and obtain the TDS curve. As the heating temperature of a sample changes, the amount of hydrogen released is also different. The TDS curve can record the hydrogen content of the same sample at different heating temperatures. Figure 4 After the test, the sample is taken out and weighed, and the total amount of hydrogen obtained by TDS curve is divided by the sample weight to obtain the hydrogen content in the sample.

[0059] It should be noted that in order to maintain the accuracy of the test method of the present invention, the following requirements need to be noted:

[0060] (a) When sampling, it is best to use the wire cutting method, and ensure that there is no obvious difference in thickness between different samples at the same thickness; leave 0.1mm grinding amount on the surface;

[0061] (b) During electrochemical hydrogen charging, it is best to connect multiple samples taken in step (1) in series, so as to ensure that the current is consistent and avoid current system errors between different hydrogen charging operations;

[0062] (c) Electrochemical hydrogen charging takes a long time, so the power supply should be continuous and uninterrupted. In case of interruption, hydrogen needs to be recharged;

[0063] (d) During the placement test, ensure that the ambient temperature is 20±5℃, the specimens are placed in a consistent posture, and cannot aggregate;

[0064] (e) When measuring hydrogen by TDS, the preparation time for the sample to enter the vacuum tube shall not exceed 10 minutes, and the difference in preparation time for different samples shall not exceed 1 minute;

[0065] (f) The weight of the sample shall be measured to an accuracy of 0.1 g and the hydrogen content shall be calculated to an accuracy of 0.01 ppm;

[0066] (g) When fitting the curve of hydrogen content changing with placement time, the correlation coefficient of the fitting formula cannot be lower than 0.8. If it is lower than 0.8, the points with large deviation need to be re-measured;

[0067] (h) When calculating the hydrogen diffusion coefficient, retain three significant figures.

[0068] The technical solution of the present invention is further explained below in conjunction with specific embodiments.

[0069] Example 1

[0070] The large forging in this embodiment is a 300 mm thick large forging of chromium-molybdenum alloy structural steel. The method for determining the hydrogen diffusion coefficient in the large-size forging of the alloy structural steel in this embodiment comprises the following steps:

[0071] (1) Sample preparation: Wire cutting was used to sample near the surface, 75 mm (1 / 4 thickness) and 150 mm (1 / 2 thickness) from the surface. Five samples were taken at the same thickness. The sample diameter was 5 mm and the length was 50 mm. The samples were ground into Figure 1 The specimen shown;

[0072] (2) Electrochemical hydrogen charging: Prepare a sufficient amount of 0.1 mol / L NaOH solution with deionized water and use a constant current power supply. Figure 2 The samples at the same thickness are charged with hydrogen in series in the manner shown, and the charging current density is 1 mA / cm 2 , current 16.5mA, hydrogen charging time 72h;

[0073] (3) Storage test: After cleaning and drying the hydrogen-filled samples, place them in a natural environment at room temperature for 12 hours, 24 hours, 48 ​​hours, and 96 hours, ensuring that the ambient temperature is 20±5°C;

[0074] (4) TDS hydrogen measurement: The hydrogen content is measured using TDS equipment from R-DEC. Figure 3 As shown, the heating rate is 100℃ / min, the heating temperature is 800℃, and the hydrogen content test results are shown in Table 1;

[0075] (5) Calculation of diffusion coefficient: Based on the hydrogen content obtained in step (4), a curve is drawn showing the change of hydrogen content at different time of sample placement at the same sampling thickness, such as Figure 5 As shown;

[0076] According to formula C t =C ∞ +(C0-C ∞ )exp(-22.2D t / d 2 )The results in Table 1 are fitted, where the results at different sampling thicknesses are shown below, and the calculated diffusion coefficients are shown in Table 2.

[0077] The fitting equations at different sampling locations are as follows:

[0078] Sampling near the surface

[0079] C t =0.01+(0.22-0.01)exp(-22.2×1.52×10 -7 t / 5 2 )

[0080] Sampling at 1 / 4 thickness

[0081] C t =0.10+(0.43-0.10)exp(-22.2×1.98×10 -7 t / 52 )

[0082] Sampling at 1 / 2 thickness

[0083] C t =0.18+(0.82-0.18)exp(-22.2×1.34×10 -6 t / 5 2 )

[0084] According to the above three fitting equations, combined with the formula, C t =C ∞ +(C0-C ∞ )exp(-22.2D t / d 2 ), the hydrogen diffusion coefficient D can be obtained. The results are shown in Table 2.

[0085] Table 1 Hydrogen content measurement results (ppm)

[0086] Placement time 1 / 2 thickness 1 / 4 thickness Near the surface 0 hours 0.82 0.43 0.22 12 hours 0.67 0.30 0.15 24 hours 0.59 0.28 0.04 48 hours 0.36 0.23 0.03 96 hours 0.18 0.10 0.01

[0087] Table 2 Hydrogen diffusion coefficient measurement results

[0088] Sampling site <![CDATA[Hydrogen diffusion coefficient D (cm 2 / s)]]> 1 / 2 thickness <![CDATA[1.34×10 -6 ]]> 1 / 4 thickness <![CDATA[1.98×10 -7 ]]> Near the surface <![CDATA[1.52×10 -7 ]]>

[0089] Example 2

[0090] The method for determining the hydrogen diffusion coefficient in a large-size forging of alloy structural steel in this embodiment is the same as that in embodiment 1, except that in step (2), the hydrogen charging current density is 6 mA / cm 2 , current 100mA, hydrogen charging time is 96h;

[0091] In step (4), the heating rate is 200°C / min and the heating temperature reaches 700°C.

[0092] After calculation, the measurement results of the hydrogen diffusion coefficient of the sampling site are shown in Table 3.

[0093] Table 3

[0094] Sampling site <![CDATA[Hydrogen diffusion coefficient D (cm 2 / s) <!-- 5 -->]]> 1 / 2 thickness <![CDATA[1.30×10 -6 ]]> 1 / 4 thickness <![CDATA[1.95×10 -7 ]]> Near the surface <![CDATA[1.55×10 -7 ]]>

[0095] Example 3

[0096] The method for determining the hydrogen diffusion coefficient in a large-size forging of alloy structural steel in this embodiment is the same as that in embodiment 1, except that in step (2), the hydrogen charging current density is 6 mA / cm 2 , current 100mA, hydrogen charging time 48h;

[0097] In step (4), the heating rate is 100°C / min and the heating temperature reaches 600°C.

[0098] After calculation, the measurement results of the hydrogen diffusion coefficient of the sampling site are shown in Table 4.

[0099] Table 4

[0100] Sampling site <![CDATA[Hydrogen diffusion coefficient D (cm 2 / s)]]> 1 / 2 thickness <![CDATA[1.31×10 -6 ]]> 1 / 4 thickness <![CDATA[1.96×10 -7 ]]> Near the surface <![CDATA[1.56×10 -7 ]]>

[0101] Test Example 1

[0102] The test was repeated according to the method of Example 1. The results of hydrogen content measurement are shown in Table 5. It can be seen that the TDS measurement results have good reproducibility.

[0103] Table 5

[0104] Placement time 1 / 2 thickness 1 / 4 thickness Near the surface 0 hours 0.81 0.42 0.23 12 hours 0.66 0.30 0.16 24 hours 0.60 0.27 0.05 48 hours 0.35 0.22 0.03 96 hours 0.19 0.10 0.01

[0105] It can be seen from Tables 1 and 5 that when the samples are placed at the same position for the same time, the hydrogen contents measured by the method of the present invention are not much different, indicating that the method of the present invention has good reproducibility.

[0106] Test Example 2

[0107] Example 1: A 300 mm thick large forging of chromium-molybdenum alloy structural steel is usually subjected to a dehydrogenation annealing process without considering the hydrogen diffusion coefficient, which includes holding at 650°C for 14 days and rapidly cooling to below 300°C for 6 days.

[0108] The hydrogen diffusion coefficients of different parts of the forging obtained in Example 1 were substituted into theoretical calculations. After 2 days of hydrogen diffusion at room temperature, the hydrogen content dropped to less than 50% of the initial content. After 4 days of hydrogen diffusion at room temperature, the hydrogen content dropped to less than 10% of the initial content, which met the requirements.

[0109] Therefore, according to the hydrogen diffusion coefficient results of the present invention and verified by experiments, the dehydrogenation annealing time of 300 mm thick large forgings of chromium-molybdenum alloy structural steel can be shortened from 20 days to 18 days, thereby improving production efficiency and saving production costs.

[0110] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for determining the hydrogen diffusion coefficient in large-size forgings of alloy structural steel, characterized in that: The method comprises the following steps: (1) Sample preparation: Take samples from the locations to be tested on large-size alloy structural steel forgings and polish the sample surfaces; (2) Electrochemical hydrogen charging: The sample is used as the cathode and Pt wire or graphite is used as the anode to perform electrochemical hydrogen charging in an alkaline solution; (3) Storage test: The hydrogen-filled samples were placed at room temperature for different periods of time; (4) TDS hydrogen measurement: Use TDS equipment to test the hydrogen content of samples at the same sampling thickness after being placed for different times; (5) Calculation of hydrogen diffusion coefficient: Based on the hydrogen content of the sample at the same sampling thickness at different placement times tested in step (4), the relationship between the sample at the same sampling thickness at different placement times and the hydrogen content is fitted according to the following formula to obtain the hydrogen diffusion coefficient; C t =C ∞ +(C0-C ∞ )exp(-22.2D t / d 2 ); Among them, C t is the hydrogen content in the sample after t hours of storage, unit: ppm; C ∞ is the hydrogen content in the sample after being placed for ≥48h, unit: ppm; C0 is the hydrogen content in the sample without being placed, unit: ppm; d is the sample diameter, unit: mm; D is the hydrogen diffusion coefficient, unit: cm 2 / s; t is the placement time, unit: h.

2. A method for determining the hydrogen diffusion coefficient in large-size forgings of alloy structural steel according to claim 1, characterized in that: In step (1), the diameter of the sample is 5 mm and the length is 50 mm.

3. The method for determining the hydrogen diffusion coefficient in large-size forgings of alloy structural steel according to claim 1, characterized in that: In step (1), at least 5 samples are taken at the same thickness position.

4. A method for determining the hydrogen diffusion coefficient in large-size forgings of alloy structural steel according to any one of claims 1 to 3, characterized in that: In step (2), the alkaline solution is a sodium hydroxide solution.

5. A method for determining the hydrogen diffusion coefficient in large-size forgings of alloy structural steel according to any one of claims 1 to 3, characterized in that: In step (2), the current in the electrochemical hydrogen charging is 10-100 mA, and the current density is 0.6-6 mA / cm 2 , continuous hydrogen charging for 48 to 96 hours.

6. A method for determining the hydrogen diffusion coefficient in large-size forgings of alloy structural steel according to claim 5, characterized in that: In step (2), multiple samples taken at the same thickness position are connected in series and then electrochemically charged with hydrogen.

7. A method for determining the hydrogen diffusion coefficient in large-size forgings of alloy structural steel according to any one of claims 1 to 3, characterized in that: In step (3), the placement time is T0 = 0h, T1 = 12h, T2 = 24h, T3 = 48h, T4 = 96h...T n =2*T n-1 , where n is an integer ≥ 2.

8. A method for determining the hydrogen diffusion coefficient in large-size forgings of alloy structural steel according to claim 7, characterized in that: In step (3), the temperature at which the sample is placed is 20±5°C.

9. A method for determining the hydrogen diffusion coefficient in large-size forgings of alloy structural steel according to claim 1, characterized in that: In step (4), when testing the hydrogen content, the heating rate is 100-200°C / min and the heating temperature is 600-800°C.

10. A method for determining the hydrogen diffusion coefficient in large-size forgings of alloy structural steel according to claim 9, characterized in that: In step (4), when testing the hydrogen content, the preparation time for the sample to enter the vacuum tube shall not exceed 10 minutes, and the difference in preparation time between different samples shall not exceed 1 minute.